СHRONIC FATRIGUE SYNDROME (Multidisciplinary Journal of Science and Technology, 2025)
Chronic Fatigue Syndrome (CFS), also known as Myalgic Encephalomyelitis (ME), is a complex and debilitating disorder characterized by profound, persistent fatigue that is not relieved by rest and is not directly caused by other medical conditions. The exact cause of CFS remains unknown, but it is believed to result from a combination of factors, including viral infections, immune system dysfunction, hormonal imbalances, and psychological stress.Common symptoms include chronic fatigue, sleep disturbances, muscle and joint pain, headaches, cognitive impairments ("brain fog"), and psychological symptoms such as depression and anxiety. Diagnosing CFS can be challenging due to the lack of specific laboratory tests and the need to rule out other conditions with similar symptoms.